EFFECT OF STRESS MANAGEMENT STRATEGIES ON EMPLOYEE PERFORMANCE NATIONAL OPEN UNIVERSITY, NIGERIA - Madu, Mavis B.; Ibeme, Nwamaka P.; Ogwuche, Mathew E.; Zakari, Dr Musa; Gaddafi, Ibrahim M. (Gorontalo State University, 2024)
The study examined stress management strategies and its effect on employee performance among academic staff of National Open University of Nigeria (NOUN). Survey and documentary research designs were employed. Survey was used to generate primary data in order to establish the relationship between stress management strategies and employee performance among academic staff in NOUN while the documentary research designs was used to obtain data from the documentary evidences. The population of the study comprises academic staff of National Open University of Nigeria. Primary data were collected through the administration of questionnaire, while secondary data were obtained from the work of past researchers and pieces of reports on the subject matter. The simple sampling technique was used to select the participants. Quantitative statistical analysis was used to test the hypotheses at 5% level of significance. Multiple regressions with the aid of SPSS version 27.0 were used to analyse the data. Person-Environment Fit Theory was adopted to explain stress management and performance. Findings revealed positive impact of functional working equipment in managing stress level and performance among academic staff members at the National Open University of Nigeria. Finding also revealed positive impact staff welfare scheme on stress levels and work performance among academic staff members at NOUN. The study recommends among others, that the Management of National Open University of Nigeria should introduce and implement more Stress Management Programs. The Management of National Open University of Nigeria should strengthen its policies aimed at promoting work-life balance for academic staff at NOUN.